2022
DOI: 10.3389/fcvm.2021.797046
|View full text |Cite
|
Sign up to set email alerts
|

Immune Mechanisms of Plaque Instability

Abstract: Inflammation crucially drives atherosclerosis from disease initiation to the emergence of clinical complications. Targeting pivotal inflammatory pathways without compromising the host defense could compliment therapy with lipid-lowering agents, anti-hypertensive treatment, and lifestyle interventions to address the substantial residual cardiovascular risk that remains beyond classical risk factor control. Detailed understanding of the intricate immune mechanisms that propel plaque instability and disruption is… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 254 publications
(442 reference statements)
0
18
0
Order By: Relevance
“…37 The inflammatory response is involved in all stages of AS development. 39 CANTOS experiment confirmed the correctness of AS inflammation theory and opened the second era of AS prevention and treatment. It focused on anti-inflammatory benefits.…”
Section: Discussionmentioning
confidence: 78%
“…37 The inflammatory response is involved in all stages of AS development. 39 CANTOS experiment confirmed the correctness of AS inflammation theory and opened the second era of AS prevention and treatment. It focused on anti-inflammatory benefits.…”
Section: Discussionmentioning
confidence: 78%
“…One limitation of our work is the use of ApoE–/– mice fed a Western diet as an AS model; the unstable plaques are not properly mimicked by this “classic” mouse model. The rupture of unstable plaques and thrombosis are the main factors leading to heart attacks and strokes. , It has been suggested that this might be because of the tiny diameter of the mouse vessels. As the vessel diameter decreases, the surface tension increases exponentially, thereby reducing the possibility of plaque rupture …”
Section: Resultsmentioning
confidence: 99%
“…52−54 The rupture of unstable plaques and thrombosis are the main factors leading to heart attacks and strokes. 54,55 It has been suggested that this might be because of the tiny diameter of the mouse vessels. As the vessel diameter decreases, the surface tension increases exponentially, thereby reducing the possibility of plaque rupture.…”
Section: 5mentioning
confidence: 99%
“…Indeed, a crucial role of activated neutrophils in the formation of unstable plaques via uncontrolled release of ROS, cytotoxic granules, matrix degrading enzymes, etc., has been demonstrated in several papers. 27 However, very little is known about mechanisms of neutrophil recruitment into the atherosclerotic aorta. To address the role of STAT4 in neutrophil migration to sites of atherosclerosis, we analyzed several aspects of neutrophil migration both in vitro and in vivo .…”
Section: Resultsmentioning
confidence: 99%